An Optical Probe Possessing Upconversion Luminescence and Hg2+‐Sensing Properties. Issue 13 (24th July 2013) - Zhang, Jin; Li, Bin; Zhang, Liming; Zhang, Ligong
Abstract A Hg2+‐selective chromophoric upconversion nanosystem is achieved by covalently grafting Rhodamine B hydrazide (RB‐hydrazide) onto upconversion luminescent nanorod core–shell structures. The prepared β‐NaYF4 nanorods are coated with silica and characterized by X‐ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy‐dispersive X‐ray analysis (EDAX), Fourier‐transform infrared spectroscopy (FTIR), and photoluminescence spectra. Under 980 nm excitation, the upconversion luminescence is sensitive towards Hg2+ because RB‐hydrazide‐Hg can efficiently absorb green upconversion emission. The prepared nanocomposites exhibit high sensitivity and selectivity towards Hg2+ over other metal ions. These results indicate that this nanosystem could be developed as a promising fluorescence probe for detecting Hg2+ ions.